Safety profile of the concomitant use of foscarnet and aerosolized pentamidine in allogeneic hematopoietic stem cell transplantation recipients. Issue 1 (9th January 2020) - Takahashi, Masaya; Takahashi, Katsuyuki; Inose, Ryo; Sugimoto, Takashi; Koh, Hideo; Hino, Masayuki; Nagayama, Katsuya
Abstract: Background: Concomitant use of foscarnet and intravenous pentamidine can very frequently cause severe hypocalcemia. However, it is unknown whether aerosolized pentamidine has a similar adverse interaction with foscarnet. The present study was aimed at examining the safety profile of concomitantly used foscarnet and aerosolized pentamidine in patients receiving allogeneic hematopoietic stem cell transplantation. Methods: Data from allogeneic hematopoietic stem cell recipients who had been administered foscarnet therapy for over 7 days were analyzed. We compared electrolyte abnormalities and serum creatinine level between patients who received aerosolized pentamidine concomitantly and those who did not. Results: A total of 84 consecutive patients and 135 episodes of foscarnet therapy between May 2011 and April 2016 were evaluable. Of these 135 episodes, 25 episodes of therapy included concurrent therapy with 300 mg dose of aerosolized pentamidine once a month (pentamidine group) and 110 episodes did not (non‐pentamidine group). The incident rates of grade 3/4 hypocalcemia did not significantly differ between the pentamidine and non‐pentamidine groups ( P  = .207; 0/25 [0%] vs 10/110 [9.1%], respectively). In addition, we observed no significant difference in the incident rates of grade 3/4 serum creatinine increase between the two groups ( P  = 1.00; 0/25 [0%] vs 4/110 [3.6%], respectively). Conclusion: Our results suggest that the drug interactions between foscarnet and aerosolized pentamidine may not be clinically significant.